Pohutu Momulanga: Gelar Adat di Gorontalo - Moh. Ihsan Husnan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
This article focuses on a traditional ceremony in Gorontalo. The so-called Pohutu Momulanga ceremony, i.e. a traditional ritual which is performed in the event of local coronation and conferral for a regent or major in Gorontalo. The study shows that there has a number of meanings and values in the Pohutu Momulanga ceremony. Among those values and meanings consist on regalia and sacred words as the symbol of tuja’i. Those symbols and the tuja’i meant as leadership examples to community. It is important to note that the Pohutu Momulanga ritual is very much influenced by Islamic values.